2013
DOI: 10.1007/s00705-013-1826-0
|View full text |Cite
|
Sign up to set email alerts
|

Cell cycle perturbations induced by human herpesvirus 6 infection and their effect on virus replication

Abstract: In this study, we demonstrate that infection of HSB-2 cells with human herpesvirus 6 (HHV-6) resulted in the accumulation of infected cells in the G2/M phase of the cell cycle. Analysis of various cell-cycle-regulatory proteins indicated that the levels of cyclins A2, B1, and E1 were increased in HHV-6-infected cells, but there was no difference in cyclin D1 levels between mock-infected and HHV-6-infected cells. Our data also showed that inducing G2/M phase arrest in cells infected by HHV-6 provided favorable … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
4
1

Year Published

2014
2014
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(5 citation statements)
references
References 33 publications
0
4
1
Order By: Relevance
“…These results differ from the results of De Bolle and coworkers, who found that late post HHV-6A infection of human cord blood mononuclear cells there was increased accumulation of cyclin A without up-regulation of cyclin E [19]. Furthermore, analysis of the regulatory proteins which are involved in the cell cycle in HSB-2 cells [20], indicated that cyclins A2, B1, E1 and MCM5 were increased in HHV-6-infected cells, but there was no difference in cyclin D1. Hence, the expression of E2F1 target genes during HHV-6A infection varies in different cells/tissues examined.…”
Section: Beta-herpesviruses Manipulate E2f-rb Pathway During Lytic Incontrasting
confidence: 85%
See 1 more Smart Citation
“…These results differ from the results of De Bolle and coworkers, who found that late post HHV-6A infection of human cord blood mononuclear cells there was increased accumulation of cyclin A without up-regulation of cyclin E [19]. Furthermore, analysis of the regulatory proteins which are involved in the cell cycle in HSB-2 cells [20], indicated that cyclins A2, B1, E1 and MCM5 were increased in HHV-6-infected cells, but there was no difference in cyclin D1. Hence, the expression of E2F1 target genes during HHV-6A infection varies in different cells/tissues examined.…”
Section: Beta-herpesviruses Manipulate E2f-rb Pathway During Lytic Incontrasting
confidence: 85%
“…Inhibition of the G 2 /M checkpoint by viruses may serve to maintain the cell in a pseudo S-like phase increasing viral replication [20]. Viruses may also utilize the DNA damage responses to maximize viral replication [27].…”
Section: Cell Cycle Arrest In Roseoloviruses Infectionmentioning
confidence: 99%
“…Although the role of the U14–p53 interaction remains unclear, it is possible that U14 induces the stabilization and functional inactivation of p53. Consistent with this, HHV-6 can induce cell-cycle arrest at G1/S or G2/M phase [ 20 , 21 , 22 , 23 , 24 , 25 ], and the HHV-6 DR6 protein has the ability to inhibit G2/M transition independently of p53 [ 31 ]; furthermore, HHV-6B U19 inhibits p53-dependent cell death [ 32 ]. Therefore, it is possible that U14 promotes cell-cycle arrest at G2/M independently of p53.…”
Section: Discussion/conclusionmentioning
confidence: 89%
“…HHV-6 infection also induces cell-cycle arrest. For example, infection of T cells with HHV-6 is associated with cell-cycle arrest at the G1/S or G2/M phase [ 20 , 21 , 22 , 23 , 24 , 25 ], and HHV-6B infection of Molt3 cells causes cell-cycle arrest at the G1 phase concomitant with accumulated and phosphorylated p53 [ 25 ]. Inhibition of cell proliferation by viruses can occur through both p53-dependent and-independent pathways [ 25 , 26 , 27 ].…”
Section: Introductionmentioning
confidence: 99%
“…Previous studies showed that IAV infection arrested A549 cells at the G0/G1 phase [49][50][51], via inhibition of S phase promoting checkpoint proteins. It is assumed that cell cycle arrest can benefit viral replication.…”
Section: Discussionmentioning
confidence: 96%